Assessment for the progressive collapse of moment resisting frame structures using a practiced-oriented method - Mohamed Nazri, Fadzli; Mou_d Kassem, Moustafa; Shahidan, Shahiron; Mohd Zuki, Sharifah Salwa; Sooria, Sherliza Zaini (ASM JOURNAL, ASM Publisher, 2018)
Abnormal loads that include explosions, vehicle accidents, bombings, and earthquakes that cause column failure may lead to progressive collapse. This study investigated the potential of progressive collapse of column removal in order to evaluate the tendency of progressive collapse between Moment Resisting Concrete Frames (MRCF) and Moment- Resisting Steel Frames (MRSF) related to the deformation of rotation degree. This study also evaluated the drift limit of damage measurement. The moment resisting frames were designed based on Eurocode (EC3) and (EC8). The response of 4-, 6- and 9-storey MRCF structures and MRSF structures using the Alternative Path Method (APM) was studied whereas the locations of columns removed at the corner and at the centre of the structures were speci ed as Case 1 and Case 2, respectively. Pushover Analysis (POA) and Incremental Dynamic Analysis (IDA) were performed using the SAP 2000 program. Two types of framed structures with single column loss in two di erent locations, i.e. corner and centre were considered in this investigation. The results showed that MRCF has a larger potential of experiencing progressive collapse than MRSF. A greater Peak Ground Acceleration (PGA) value was obtained by Case 2 before it reached the Collapse Prevention Limit. Therefore, this nding revealed that column loss at the corner of buildings causes a higher risk of progressive collapse compared to column loss at the centre of buildings.